Management Coaching Model and Impact of its Activities on Employee Satisfaction - Cajnko, Petra; Kraljić, Suzana (LeXonomica, 2018)
The article tries to answer the research question: What is the potential additive effect on employee satisfaction when using management coaching model and its activities? The purpose of the article has been to form a model of management coaching and of the influence of its activities on employee satisfaction based on theory review and field study results. We have confirmed the main hypothesis (H1: Implementing management coaching model positively influences employee satisfaction) and all of the secondary hypotheses (Hi,j: Implementing activity »i« of the management coaching model positively influences factor »j« of employee satisfaction; i = 1, 2, 3, 4, 5; j = 1, 2, 3, 4, 5) with our empirical study, focused on the employees. The topic is of practical value and it will help managers in Slovenia and abroad understand the effect of the activities of coaching on employee satisfaction. Managementski model coachinga in vpliv njegovih aktivnosti na zadovoljstvo zaposlenihV članku smo poskušali odgovoriti na temeljno raziskovalno vprašanje: Kakšen je potencialni dodatni učinek na zadovoljstvo zaposlenih z uporabo managementskega modela coachinga in aktivnosti, ki jih zajema model? Namen našega članka je na temelju teorije s tega področja in spoznanj iz terenske raziskave oblikovati managementski model coachinga in vpliva njegovih aktivnosti na zadovoljstvo zaposlenih. Z empirično raziskavo smo potrdili glavno hipotezo (H1: Izvajanje managementskega modela coachinga pozitivno vpliva na zadovoljstvo zaposlenih.) in vse pomožne hipoteze (Hi,j – izvajanje i–te aktivnosti managementskega modela coachinga pozitivno vpliva na j–ti dejavnik zadovoljstva zaposlenih; i = 1, 2, 3, 4, 5; j = 1, 2, 3, 4, 5.). Na podlagi zgoraj napisanega lahko sklepamo, da je tema izjemno aktualna, njeni rezultati pa bodo omogočili slovenskim in tudi drugim managerjem razumeti pomen in vpliv aktivnosti coachinga na zadovoljstvo zaposlenih.